La Seconda guerra mondiale sugli schermi: un’analisi sul cinema nel Nordeste - Andreza Santos Cruz Maynard si è addottorata in Storia presso l’Universidade Estadual Paulista (UNESP) ed è attualmente post-dottoranda presso la Universidade Federal do Rio de Janeiro (UFRJ). È membro del Grupo de estudo do tempo presente (GET) dell’Universidade Federal de Sergipe. (Diacronie. Studi di Storia Contemporanea, 2014)
This paper analyzes the relationship between the cinemas located in the city of Aracaju (located in Brazil’s Northeast) and the movies shown at the time of World War II. The cinemas’ scheduling varied according to changes in U.S. movie production, and it also depended on the international position of Brazil, considering the War and the countries involved in the conflict. Newspapers and magazines constitute the bulk of the documentation that supports an analysis of the films exhibition at a time when the mass media were controlled with political purposes.